CD19 and immunophenotype of bone marrow plasma cells in monoclonal gammopathy of undetermined significance. Issue 6 (June 1995) - Zandecki, M; Facon, T; Bernardi, F; Izydorczyk, V; Dupond, L; François, M; Reade, R; Iaru, T; Bauters, F; Cosson, A
Abstract : AIMS–To determine whether a particular phenotype or antigen is preferentially related to monoclonal gammopathies of undetermined significance (MGUS). METHODS–Bone marrow specimens from 56 patients with MGUS were stained immunocytochemically (ABC peroxidase) for CD38, CD56, CD9, CD10, CD19, CD20, CD22, and MB2. Specimens from patients recently diagnosed with multiple myeloma and reactive bone marrow samples were studied in parallel. RESULTS–CD38 was expressed on all plasma cells from all MGUS samples tested, while 36% were positive for CD56, CD9 and MB2 were both expressed strongly; CD20 was moderately expressed, and staining for CD10 and CD22 was uncommon. For these five B cell antigens there was no clear difference between their expression in MGUS and in multiple myeloma. A great difference was found for CD19: in MGUS this antigen was expressed on 2-91% of plasma cells (mean 35%) and 77% patients had > 10% positive plasma cells; in multiple myeloma its expression was low and only 12% patients had > 10% positive plasma cells. When these results were converted to numbers of CD19 positive plasma cells per 100 nucleated bone marrow cells, reactive bone marrow and MGUS specimens had a similar number of positive plasma cells. There was no correlation between expression of any of the antigens tested. CONCLUSIONS–Many of the so-called pre-B, B or activation antigens are present on plasma cells from MGUS specimens, and expression of CD9, CD10, CD20, CD22, MB2, and CD38 in MGUS was very similar to that in multiple myeloma. CD56 was frequently expressed in MGUS. In this series CD19 was highly expressed in MGUS but not in multiple myeloma. Plasma cells bearing this antigen could represent the non-neoplastic process and determination of its expression could be useful for the diagnosis of MGUS.